Evaluation of the VKORC1 haplotypes in individualising warfarin therapy / Mohd Zaki Salleh, Teh Lay Kek and Fazleen Haslinda Mohd Hatta - Salleh, Mohd Zaki; Teh, Lay Kek; Mohd Hatta, Fazleen Haslinda (2010)
Coumarin derivatives such as warfarin are the therapy of choice for the long-term treatment and prevention of thromboembolic events. Warfarin is administered orally as a racemic mixture of two enantiomers. It has very narrow therapeutic windows and large individual variability. The amount of dose needed to achieve therapeutic efficacy varies across the population due to differences in the genetic makeup of individual patients. Polymorphism of the VKORCl gene is one of the genetic factors that caused altered sensitivity to warfarin or warfarin resistance. Ten common SNPs have been identified, at positions 381, 861, 2653, 3673, 5808, 6009, 6484, 6853, 7566, and 9041 of the VKORCl reference sequence (Gen Bank accession number AY587020). Five major haplotypes were derived and haplotypes HI and H2 were assigned to group A which requires low warfarin dose while haplotypes H7, H8 and H9 were assigned to group B and require high-warfarin dose. Objective: To develop genotyping method for detection often variants of VKORCl gene and establish the distribution of VKORCl haplotypes among patients prescribed with warfarin and study the relationship of haplotypes and warfarin dose, INR and bleeding.